A risk assessment model of WSMC projects under emergencies. Issue 2 (4th October 2021) - Wang, Xiaosheng; Li, Wei; Guo, Haiying; Li, Ran
Abstract: As a novel market-based water-saving mechanism, the Water Saving Management Contract (WSMC) project faces interruption risk caused by emergencies like the coronavirus disease-2019 (COVID-19) pandemic. An interruption risk assessment model of WSMC projects is established through a quantitative evaluation of the impact of emergencies on water users based on input-output theory. First, the concept of the interruption risk index (IRI) is defined as a function of the duration of enterprise shutdown (DES). Second, the DES is divided into two parts: the duration caused by COVID-19 and that under other types of emergencies. Third, the risk tolerance threshold is given to estimate the interruption result, and its different consequences are discussed. Finally, a WSMC project in China is taken as a case study, and its interruption risks are analysed. The results show that the IRIs of this WSMC in both 2020 and 2021 are theoretically greater than the risk tolerance thresholds, and the high pandemic prevention standards and conservative pandemic estimates are the main reasons for the above results. The model established in this study provides a reference for WSMC participants to deal with emergencies and provides the theoretical support for the extension of the WSMC. HIGHLIGHTS: Firstly a quantitative interruption risk assessment model was established for WSMC. The economic loss of water users can be estimated under COVID-19 pandemic. Based on statistical data, the conditional expectation of shutdown time can be obtained under normal emergencies.